Delayed formation of intercostal artery pseudoaneurysm following trocar injury in laparoscopic radical nephrectomy - Atsushi Wanifuchi; Ippei Muranaka; Kohei Hashimoto; Naoya Masumori (Urology Case Reports)
Pseudoaneurysm of intercostal artery following laparoscopic nephrectomy is rare. We report a 69-year-old man who developed pseudoaneurysm of intercostal artery 2 months after undergoing laparoscopic right radical nephrectomy. On follow-up, patient presented with an expanding palpable mass under 5-mm trocar wound. Color Doppler ultrasound showed bidirectional blood flow in sac, and dynamic contrast-enhanced CT confirmed the pseudoaneurysm. Aneurysmectomy was performed after ligating proximal feeding artery and confirming the disruption of blood supply into sac on color Doppler ultrasound.